2017
DOI: 10.1038/s41598-017-11252-7
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Endoplasmic Reticulum Stress in Granulosa Cells from Patients with Polycystic Ovary Syndrome Contributes to Ovarian Fibrosis

Abstract: Recent studies report the involvement of intra-ovarian factors, such as inflammation and oxidative stress, in the pathophysiology of polycystic ovary syndrome (PCOS), the most common endocrine disorder of reproductive age women. Endoplasmic reticulum (ER) stress is a local factor that affects various cellular events during a broad spectrum of physiological and pathological conditions. It may also be an important determinant of pro-fibrotic remodeling during tissue fibrosis. In the present study, we showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 58 publications
5
67
0
Order By: Relevance
“…knowledge, to date, the regulation of TGF-β1 expression in granulosa cells is largely unknown. It has been shown that endoplasmic reticulum (ER) stress induces TGF-β1 expression in hGL cells 48 . Interestingly, ER stress stimulates VEGF expression in hGL cells, and inhibition of ER stress decreases VEGF expression in a rat OHSS model 49 .…”
Section: Discussionmentioning
confidence: 99%
“…knowledge, to date, the regulation of TGF-β1 expression in granulosa cells is largely unknown. It has been shown that endoplasmic reticulum (ER) stress induces TGF-β1 expression in hGL cells 48 . Interestingly, ER stress stimulates VEGF expression in hGL cells, and inhibition of ER stress decreases VEGF expression in a rat OHSS model 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it has been envisaged that the stroma of the ovaries with PCOS is expected to be stiffened due to the increase of teca cells and the thickened fibrotic albuginea. In animal experiments, the presence of fibrosis in ovarian tissue was histopathologically revealed [37][38][39][40][41]. In humans, fibrosis in the ovarian tissue can be demonstrated non-invasively with elastography [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of BGP-15 has been investigated in PCOS, as an ER stress inhibitor [48], in oxaliplatin therapy induced skeletal myopathy and ROS production [49], and in oxaliplatin induced intestinal dysfunction [50]. The investigations were carried out on BALB/c mice.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Reduction of interstitial fibrosis and collagen deposition in the ovaries [48] 3 mg/100g of body weight (BGP-15)…”
Section: Main Effect Dosementioning
confidence: 99%